Melatonin alleviates cadmium‐induced liver injury by inhibiting the TXNIP‐NLRP3 inflammasome. Issue 3 (10th March 2017) - Cao, Zhengwang; Fang, Yiliang; Lu, Yonghui; Tan, Dunxian; Du, Changhong; Li, Yuming; Ma, Qinlong; Yu, Junmei; Chen, Mengyan; Zhou, Chao; Pei, Liping; Zhang, Lei; et al.
Abstract: Cadmium (Cd) is a persistent environmental and occupational contaminant that accumulates in the liver and induces oxidative stress and inflammation. Melatonin possesses potent hepatoprotective properties against the development and progression of acute and chronic liver injury. Nevertheless, the molecular mechanism underlying the protective effects of melatonin against Cd‐induced hepatotoxicity remains obscure. In this study, we aimed to investigate the effects of melatonin on Cd‐induced liver inflammation and hepatocyte death. Male C57BL/6 mice were intraperitoneally injected with melatonin (10 mg/kg) once a day for 3 days before exposure to CdCl2 (2.0 mg/kg). We found that Cd induced hepatocellular damage and inflammatory infiltration as well as increased serum ALT/AST enzymes. In addition, we showed that Cd triggered an inflammatory cell death, which is mediated by the NOD‐like receptor pyrin domain containing 3 (NLRP3) inflammasome. Moreover, melatonin treatment significantly alleviated Cd‐induced liver injury by decreasing serum ALT/AST levels, suppressing pro‐inflammatory cytokine production, inhibiting NLRP3 inflammasome activation, ameliorating oxidative stress, and attenuating hepatocyte death. Most importantly, melatonin markedly abrogated Cd‐induced TXNIP overexpression and decreased the interaction between TXNIP and NLRP3 in vivo and in vitro. However, treatment with siRNA targeting TXNIP blocked the protective effects of melatonin in Cd‐treated primary hepatocytes. Collectively, our results suggest that melatonin confers protection against Cd‐induced liver inflammation and hepatocyte death via inhibition of the TXNIP‐NLRP3 inflammasome pathway.